Oligohydramnios Causes and Pregnancy Outcome - Third trimester versuss Second Trimester and Signficance of Amniotic Fluid Index (AFI) - Jabeen, Sadaqat; Shafqat, Tanvir; Ahmad, Shafiq (Journal of Postgraduate Medical Institute, 2011)
Oligohydramnios is a complication of high risk pregnancy which is associated with poor perinatal outcome. 50 cases of oligohydramnios were taken at random, 39 were in third trimester and II in second trimester. The commonest cause was hypertensive disorders followed by PROM (pre-mature rupture of membranes). pregnancy out come was better in the 3rd trimester, resulting in 6 (15%) deaths only as compared to 2nd trimester, where all (100%) pregnancies ended in intrauterine deaths. No pregnancy could be prolonged beyond two weeks in cases of 2nd trimester.